Compatibility and horticultural performance of Pera sweet orange clones grafted to Swingle citrumelo rootstock - Fadel, Andre Luiz (2019)
Despite its interesting agricultural traits, Swingle citrumelo (Citrus paradisi Macfad. 'Duncan' x Poncirus trifoliata L. Raf.) rootstock exhibits severe incompatibility when grafted with Pera sweet orange [Citrus sinensis (L.) Osb.] scions, and this fact limits its use for propagation purposes. Nonetheless, the existence of certain Pera sweet orange clones that are compatible with Swingle citrumelo represents a substantial gain for the entire citrus industry. This study investigated the compatibility between seven Pera sweet orange clones and Swingle citrumelo rootstock, regarding the presence of a necrotic line at the graft union junction, the difference in diameter between rootstock and scion, the influence of clonal cleaning by micrografting, and the horticultural performance of the selected combinations. No trees died because of grafting incompatibility, even after twenty years (trial I), except for clone CV1, or after six years and nine months (trial II) from planting. The rootstock/scion trunk diameter ratio was not related to the presence of a necrotic line in the graft-union region. Additionally, these variables did not influence fruit yield and quality, and they were not affected by clonal cleaning or preimmunisation of the old Pera sweet orange clones.